2007
DOI: 10.1021/ja075568n
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Xenon on Fullerene Reactions

Abstract: Solutions containing 3He@C60, 129Xe@C60, and varying amounts of 9,10-dimethylanthracene (DMA) were allowed to reach equilibrium, and the 3He and 129Xe NMR spectra were taken at the same temperature. Each spectrum showed peaks for the unreacted X@C60 and for the monoadduct. The ratios of the peak heights show that the included xenon atom substantially changes the equilibrium constant. This change is temperature dependent, meaning that the xenon atom changes both DeltaH and DeltaS for the reaction. DMA is more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 14 publications
1
44
0
Order By: Relevance
“…Frunzi, Cross, and Saunders explored experimentally the exohedral reactivity of these single‐Ng compounds. They performed the Diels–Alder reaction between 9,10‐dimethylanthracene (DMA) and 129 Xe@C 60 or 3 He@C 60 to investigate the effect of the trapped noble gas 19. They observed that the thermodynamics of the Diels–Alder reaction was favored at low temperatures in the case of 3 He@C 60 , while at high temperatures the equilibrium constant of the reaction was larger for 129 Xe@C 60 .…”
Section: Introductionmentioning
confidence: 99%
“…Frunzi, Cross, and Saunders explored experimentally the exohedral reactivity of these single‐Ng compounds. They performed the Diels–Alder reaction between 9,10‐dimethylanthracene (DMA) and 129 Xe@C 60 or 3 He@C 60 to investigate the effect of the trapped noble gas 19. They observed that the thermodynamics of the Diels–Alder reaction was favored at low temperatures in the case of 3 He@C 60 , while at high temperatures the equilibrium constant of the reaction was larger for 129 Xe@C 60 .…”
Section: Introductionmentioning
confidence: 99%
“…As a related study, 129 Xe@C 60 was reported to exhibit smaller equilibrium constant in an addition reaction with DMA than that of 3 He@C 60 [78]. The encapsulated 129 Xe atom was suggested to have substantial interaction with C 60 and slightly change the electron distribution of C 60 [78].…”
Section: Diels-alder Reaction Of (H 2 ) 2 @C 70 and H 2 @C 70mentioning
confidence: 79%
“…The encapsulated 129 Xe atom was suggested to have substantial interaction with C 60 and slightly change the electron distribution of C 60 [78]. Theoretical calculations (MPWB1K/6-31G ÃÃ ) [79] of (H 2 ) 2 @C 70 and H 2 @C 70 showed that the longer axis of the C 70 cage of (H 2 ) 2 @C 70 is elongated only by 0.02 A , while the shorter axis is shortened by 0.02 A , as compared to those of H 2 @C 70 .…”
Section: Diels-alder Reaction Of (H 2 ) 2 @C 70 and H 2 @C 70mentioning
confidence: 99%
“…Recently, the development of the molecular surgery technique has allowed molecules, such as H 2 [12][13][14] and H 2 O [15], to be inserted into fullerene cages. Inside the cages, these molecules are expected to exhibit unusual physical properties that are absent in their isolated form because of the interaction between the encapsulated molecules and the fullerene cages [16,17], as in the case of encapsulated molecules inside carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%